Effect of Knee Osteoarthritis on Quality-of-Life among Postmenopausal Females - Ramash Anmool, Fatima Chaudhary, Hira Rauf, Ayaz Khan, Umar Ibrahim, Zil E Huma, Saba Mengal, Nasir Khan, Saleh Shah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Some observational evidence suggests an effect of hormones on Osteoarthritis (O.A.), especially in premenopausal women. Aim: To determine the frequency of knee osteoarthritis among postmenopausal females. Secondly, assess the symptoms and severity of stiffness and pain. Thirdly, to assess the effect of Osteoarthritis on quality of life. Methods: The study was conducted among 50 patients with knee osteoarthritis among postmenopausal females. Aged above 45 years were included in the study. Male Participants with Amenorrhea and Traumatic Knee Injury were excluded from the study. The non-probability sampling was used for sample selection. The sample size was calculated using an open-Epi tool. Results: Most women with symptoms sometimes and often in knee osteoarthritis experience moderate and severe knee pain in rest and activity. Most women have moderate and severe difficulty in activities of daily living, difficulty in sport and recreation function, and disturbance in their quality of life in knee osteoarthritis of postmenopausal women. This study can help raise awareness and provide valuable insights into the challenges and limitations that postmenopausal women with knee osteoarthritis face daily. This can help develop more targeted and effective interventions that address the unique needs of this population. Conclusion: The study concludes that postmenopausal females have knee osteoarthritis that produces symptoms with severe pain. Their functional, daily, sports and recreational activities are moderately affected by the quality-of-life effects. Keywords: Knee Osteoarthritis, Postmenopausal women, Rehabilitation, Quality of life, Stiffness, Pain